Konservasi Kupu-kupu Papilio demoleus Linn. (Lepidoptera: Papilionidae) dengan Teknologi Makanan Buatan - Sri Nur Aminah Ngatimin; Syatrawati Syatrawati; Asmawati Asmawati (Jurnal Hutan dan Masyarakat, 2020)
The purpose of the research is to study and increase of lime butterfly (Papilio demoleus L.) population used artificial diets, then avoid endangered species status of butterfly in nature. For the future, result of research giving more information about mass rearing techniques of P. demoleus butterflies using artificial diet. P. demoleus larvae and pupae were collected from pomelo (Citrus maxima L.) in the yard of  communities in the Pattunuang Resort, Maros district, South Sulawesi. The pomelo leaves as  the main food source of P. demoleus larvae taken from the farm around Bontomate'ne village, Pangkep district, South Sulawesi. The experimental activities were conducted in the Pest Laboratory, Pests and Plant Diseases Department, Faculty of Agriculture, Hasanuddin University from February to April 2019. The treatment for P. demoleus larvae were: P0 = fresh pomelo leaves (control); P1 = 35% red bean flour + 35% pomelo leaves + 30% vitamin, water agar, and other ingredients; P2 = 25% red bean flour + 25% soybean flour + 25% pomelo leaves + 25% vitamin, water agar, and other ingredients. Ten 2nd instar of P. demoleus larvae were placed in the plastic containers (diameter = 8 cm, height = 6 cm) covered with gauze, respectively. The fresh pomelo leaves given in whole form, while artificial diet in gel form given as much as 5 g for each larvae in the container. Every day the container was cleaned from food and larvae faeces. The experiments were arranged in  Randomized Block Design with four treatments and ten replications. The result was showed P0 is the highest number increasing body weight of P. demoleus larvae. The second  highest  result  increasing  P. demoleus  body weight was showed by P2 since 2nd instar (0.74 g) until four instar (0.87 g). Observation body length of P. demoleus, P0 was showed the highest number increasing the parameter. The second highest result of body length was showed at P2 started 2nd instar (0.24 cm) through four instar (1.72 cm). Findings at  sex ratio and survival,  P0 was showed the highest number adult of P. demoleus (8 individual), P2 (3 individual) and P1 (1 individual), respectively. The highest sex ratio  of female P. demoleus resulted by P0 (3 individual), P2 (1 individual), respectively. The conclusion is : P2 made from red bean flour + soy bean flour + leaves of pomelo increasing body weight and length of P. demoleus larvae. P1 (red bean flour + leaves of pomelo) treatment was showed the lowest number in development of P. demoleus.